The crystal structure of 2-(2-hydroxy-4-n-octyloxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, C33H39N3O2 - Liu Jieying; Liu Guanghui; Lu Cuiying; Dang Rui; Kang Yuhong; Zhang Zhifang (Zeitschrift für Kristallographie - New Crystal Structures, 2025)
C33H39N3O2, monoclinic, P21/n (no. 14), a = 15.6706(4) Å, b = 4.02399(11) Å, c = 43.4356(11) Å, β = 99.098(3)°, V = 2,704.53(13) Å3, Z = 4, R gt(F) = 0.0423, wR ref(F 2) = 0.1224, T = 100 K.